2011
DOI: 10.1366/10-06024
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and X-Ray Diffraction Study of Structural Disorder in Cryomilled and Amorphous Griseofulvin

Abstract: Structural disorder induced by cryogenic milling and by heating to the amorphous phase in the active pharmaceutical ingredient Griseofulvin has been studied using Raman spectroscopy, X-ray powder diffraction (XRPD), and fluorescence spectroscopy. A broad, exciting-frequency-independent scattering background in the Raman spectra and changes in intensities and splitting of some of the Raman lines due to lattice and molecular modes have been observed. In the cryomilled samples this strong background is deconvolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…Figure 4 illustrates the Raman spectra of as-received GF, the spray-dried formulation with a 1:3 GF:polymer ratio, and the corresponding PMs. The spectra of as-received GF and PMs of GF agree well with the Fourier transform Raman data of Feng et al [64] and Raman data ofŻarów et al [65] for crystalline GF. In the Raman lines of the GF crystals, the spectral range from 1550 to 1800 cm −1 corresponds to the C=O stretching vibrational frequencies and displays a characteristic triplet of lines.…”
Section: Formulation Idsupporting
confidence: 86%
“…Figure 4 illustrates the Raman spectra of as-received GF, the spray-dried formulation with a 1:3 GF:polymer ratio, and the corresponding PMs. The spectra of as-received GF and PMs of GF agree well with the Fourier transform Raman data of Feng et al [64] and Raman data ofŻarów et al [65] for crystalline GF. In the Raman lines of the GF crystals, the spectral range from 1550 to 1800 cm −1 corresponds to the C=O stretching vibrational frequencies and displays a characteristic triplet of lines.…”
Section: Formulation Idsupporting
confidence: 86%
“…A study of structural disorder in cryo-milled amorphous drug reported the Raman spectra of micronized crystalline and various amorphous forms [33]. The changes described in this paper on going from amorphous to crystalline material are similar to those observed in this study (noting that the different excitation Fig.…”
Section: Characterisation Of Griseofulvin Tabletssupporting
confidence: 82%
“…There are three reported crystalline polymorphic forms of griseofulvin: the stable form I and the metastable forms II and III [32]. The amorphous form of griseofulvin can be prepared either by quench cooling or cryomilling [33,34]. The crystallization of amorphous forms of griseofulvin has previously been characterized using XRPD, DSC and isothermal microcalorimetry [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the Raman spectra of HPMC, griseofulvin, and clusters of griseofulvin found within the film. The boxed region indicates the spectral region with the strong 1620 cm −1 griseofulvin band 25. The griseofulvin cluster spectrum was obtained directly from Film 3 regions wherein the 1620 cm −1 band had a high intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Higher spatial resolution is therefore obtained by micro‐Raman mapping, and this method could also eventually detect the presence of inhomogeneity, impurities, and/or API polymorphs in the films 12,26. The spectra obtained were compared with those from a prior study wherein the structural disorder induced by cryogenic milling and by heating to the amorphous phase of the API were studied using Raman spectroscopy, X‐ray powder diffraction, and fluorescence spectroscopy 25. For griseofulvin films, Raman mapping analysis did not show a solid phase transition such as amorphization upon film formation, as determined by the enhanced intensity of a characteristic Raman line for crystalline griseofulvin at 830 cm −1 reported by Zarow et al25…”
Section: Resultsmentioning
confidence: 99%